Toward a material culture of Jewish loss. Issue 1 (2nd January 2017) - Gerlach, David
Abstract: What can physical objects tell us about the Holocaust and the experience of survivors? Studies of Jewish restitution mostly focus on the political debates and negotiations for postwar compensation, as well as institutions and actors involved in these discussions. While individual claimants might be used as examples of particular trends in studies of restitution, we lack a matrix to chart the meaning of individual claims in relation to the overall scope of Jewish reparations. This paper explores the nature of individual property claims in an effort to sketch out a material culture of Jewish loss. Although material culture studies tend to explore how goods reflect everyday life and culture, this paper uses this approach to study the personal, political and socio-economic meanings of wartime theft and postwar restitution.